Lenguaje escrito y tecnologia - Peronard, Marianne (Boletín de Filología, 2006)
The present article airns to give a brief survey of sorne of the most irnportant technological changes which have affected the concept and use of natural language From the first and probably most important of these changes, the invention of writing, to more recent ones, sucli as television and hypei-text, there have always been people who were in favor of their introduction and people against thein, especially because of their possible effects on the mental process related to the use of language. Yet, scientific studies on the matter have been rather scarce and no clear conclusion has been reached. Now that the computer has found its place in our educational system, it is really irnportant and urgent to study systematically whether the technologies associated with it hinder or favor the leaming of our students.